Failing to reach the poorest: Subnational financing inequalities and health and education outcomes - Amy Dodd; Marcus Manuel; Zach Christensen (Overseas Development Institute (ODI), 2019)
Investments in health and education are vital in reducing inequalities of opportunity and outcome, developing a country's human capital and improving lives, all of which contribute to broader economic benefits. Subnational finance has an important role to play in addressing the challenges of access to, and the quality of education and healthcare for, the poorest people. Building on previous Overseas Development Institute and Development Initiatives research, this report assesses how well subnational financing of health and education in all 82 low- and middle-income countries, including all Least Developed Countries, targets the worst health and education outcomes. The report recommends that: governments and education donors should learn from why donor aid for health seems to be so much better targeted; government and education donors should commit to improve the targeting of their financial resources; at a minimum, the equal allocation of government spending between regions and above-national-average spend should be ensured for education aid in the worst-performing regions.
Keywords: 330